Iceland’s “Egg of Life” and the Modern Media - Kristmannsson, Gauti (Meta, 2004)
This paper provides an overview of Icelandic language politics in the face of the challenges brought on by the modern media in a small country. It starts with a short glance at the beginnings of Icelandic linguistic politics in the nineteenth century to reveal the basic ideological premises and show how they have been maintained in national discourse on the Icelandic language and the media. It then examines how the Icelandic national consensus on linguistic purism has been shaken by technological and political developments, in short the advancing globalisation of the media. These developments are reflected in the practices of media translation and changing attitudes towards translation. L’étude présente un aperçu de la politique linguistique en Islande qui, en sa qualité de petit pays, est particulièrement sensible à la confrontation avec les médias modernes. Elle débute par un bref historique de la politique linguistique islandaise, qui puise ses racines au XIXe siècle, afin d’introduire ses bases idéologiques et de démontrer à quel point ces dernières ont pu perdurer dans le débat national sur la langue et les médias. Elle traite ensuite de la manière dont le consensus sur le purisme linguistique a souffert des développements politiques et technologiques, bref de la mondialisation des médias. Ces développements transparaissent dans les pratiques de traduction des médias ainsi que dans l’approche évolutive de la traduction.